O papel social da igreja cristã na prevenção do uso indevido de drogas na adolescência: da problematização a uma proposta de ação - Camargo, Caroline Cristine Costa (2013)
This is a proposition for an action from a faith perspective in relation to the prevention of the improper use of drugs during adolescence and to the importance of the involvement of the Christian church in favor of social actions as a social network and a space of great influence in the families. The study works with theoretical bibliographical research, from which a dialog was established based on the data from the VI National Survey About the Consumption of Psychotropic Drugs among Students of Grade School and Middle Education of the Public and Private Teaching Networks in the 27 Brazilian Capitals of 2010. Following this it analyzes the data of the city of Campo Grande/MS, from the above mentioned study, which highlighted that it is in adolescence where the first use of drugs occurs. In this first part, some concepts about adolescence as a phase of discovery and physical and emotional changes are presented, indicating what are the types of drugs in existence, as well as which ones are preferred during this age bracket. In the second part, the study points to the role of the State and of civil society, the role of the family and of the church as part of the social network and their respective responsibilities with regard to the prevention of improper use of drugs in adolescence. The third and last part brings, yet, a dialog about the role of the church in a faith and love perspective emphasizing the actions of Jesus and, consequently, a proposal for social action to be carried out in the Christian churches. During the production of this paper, an exchange was established with legislations, psychology authors, social services and theology.